The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1834-7819.2007.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of casein phosphopeptide‐amorphous calcium phosphate on remineralization of artificial caries‐like lesions: an in vitro study

Abstract: Background:  The aims of this study were to investigate the efficacy of CPP‐ACP containing Tooth Mousse on the remineralization of enamel lesions and to compare its efficacy to that of a fluoride‐containing toothpaste.Methods:  Permanent teeth were placed in demineralizing solution for 96 hours to produce artificial caries‐like lesions 120–200 μm in depth. They were sectioned into 100–150 μm thick samples and randomly assigned to five groups: for Group A, a fluoridated toothpaste (1100 ppm) was used as a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(214 citation statements)
references
References 20 publications
18
164
0
15
Order By: Relevance
“…Whereas in the present study, the CPP-ACP and CPP-ACFP crèmes were used as an adjunct to the fluoride treatment with 1450 ppm F. In their study, Kumar, et al (2008), revealed an additive effect for the application of the CPP-ACP crème after the fluoride toothpaste treatment, which is consistent with the results of the current study, however it was not reported whether this additional effect was statistical significance or not.…”
Section: Effect Of Cpp-acp and Cpp-acfp On Remineralising Enamel Subssupporting
confidence: 81%
See 1 more Smart Citation
“…Whereas in the present study, the CPP-ACP and CPP-ACFP crèmes were used as an adjunct to the fluoride treatment with 1450 ppm F. In their study, Kumar, et al (2008), revealed an additive effect for the application of the CPP-ACP crème after the fluoride toothpaste treatment, which is consistent with the results of the current study, however it was not reported whether this additional effect was statistical significance or not.…”
Section: Effect Of Cpp-acp and Cpp-acfp On Remineralising Enamel Subssupporting
confidence: 81%
“…The positive effect of CPP-ACP (Tooth Mousse) and CPP-ACFP (MI Paste Plus) in the remineralisation of enamel lesions has been shown in previous in vitro studies (Kumar et al, 2008, Jayarajan et al, 2011, Zhang et al, 2011. However, different methodologies were used in these studies compared to the current study.…”
Section: Effect Of Cpp-acp and Cpp-acfp On Remineralising Enamel Subsmentioning
confidence: 98%
“…CPP-ACP products have shown an ability to prevent dental demineralization and increase remineralization of enamel and dentin in vitro (12,13), as well as to arrest initial enamel caries lesions in vivo (15)(16)(17). However, due to the lack of clinical trials, there is no consensus about the cariostatic effect of CPP-ACP.…”
Section: Discussionmentioning
confidence: 94%
“…Pastes containing a complex of casein phosphopeptide (CPP) and amorphous calcium phosphate (ACP), with or without fluoride, have shown potential to prevent dental demineralization, increase remineralization in vitro (10)(11)(12)(13)(14) and to repair initial enamel caries lesions in vivo as well (15)(16)(17). It has been suggested that casein phosphopeptides (CPP) have the ability to stabilize calcium phosphate in solution by binding amorphous calcium phosphate (ACP) with their multiple phosphoserine residues, thereby allowing the formation of small CPP-ACP clusters (18).…”
Section: Introductionmentioning
confidence: 99%
“…Traces of demineralization, which cannot be foreseen, are often discovered at the end of treatment, requiring continued preventive fluoride treatment. In this case it is important to make topical applications of fluorides in a solution, gel or varnish to facilitate surface remineralization of incipient carious lesions [49,50]. Another study concerning remineralization with fluoride after removal of orthodontic devices has shown that the use of a fluoride toothpaste twice a day leads to remineralization after 2 months, and combining fluoride toothpaste and fluoride gels speeds up remineralization (1 month) [51].…”
Section: After the Orthodontic Treatmentmentioning
confidence: 99%